2020
DOI: 10.1123/jmpb.2019-0060
|View full text |Cite
|
Sign up to set email alerts
|

Where to Place Which Sensor to Measure Sedentary Behavior? A Method Development and Comparison Among Various Sensor Placements and Signal Types

Abstract: Background: Sedentary behavior (SB) is associated with several chronic diseases and office workers especially are at increased risk. SB is defined by a sitting or reclined body posture with an energy expenditure of ≤1.5 metabolic equivalents. However, current objective methods to measure SB are not consistent with its definition. There is no consensus on which sensor placement and type should be used. Aim: To compare the accuracy of newly developed artificial intelligence models for 15 sensor placements in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Since all included participants were office workers, it seems that the activPAL+ might be the better choice for studies focusing on office work (the domain in which our participants spent most of their time from 08:00 to 16:00 on weekdays), while the sensor choice has less bearing for the time after 17:00 on weekdays and for weekend days. This observation confirms the results of a previous laboratory study in which we noticed the highest accuracy for lower-body sensors to measure both components of sedentary behaviour in desk based office work [ 27 ] and adds the information that this does not directly translate to outside the office. In this regard, it is important to note that the bias of the activPAL perfectly reflects active sitting (which was spread throughout the day), while the bias of the ActiGraph almost perfectly reflects inactive standing (which was most dominant between 08:00 and 16:00) [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Since all included participants were office workers, it seems that the activPAL+ might be the better choice for studies focusing on office work (the domain in which our participants spent most of their time from 08:00 to 16:00 on weekdays), while the sensor choice has less bearing for the time after 17:00 on weekdays and for weekend days. This observation confirms the results of a previous laboratory study in which we noticed the highest accuracy for lower-body sensors to measure both components of sedentary behaviour in desk based office work [ 27 ] and adds the information that this does not directly translate to outside the office. In this regard, it is important to note that the bias of the activPAL perfectly reflects active sitting (which was spread throughout the day), while the bias of the ActiGraph almost perfectly reflects inactive standing (which was most dominant between 08:00 and 16:00) [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…The indirect calorimeter recorded with 0.1 Hz in the mixing chamber mode. Note that the study included additional sensors not used for the present analysis and thus reported elsewhere [42]. The participants completed the four tasks at each of the three workplaces in random order, ensuring that the same task and workplace never occurred in succession.…”
Section: Experimental Procedures and Equipmentmentioning
confidence: 99%
“…For each task, only steady state data was considered. The onset of steady state was defined by the first minute with less than 10% deviation from the median of all subsequent minutes, but earliest after one and latest after 4 min [42]. All minutes of each task were furthermore assigned into the prescribed posture (sitting for the conventional and activity-promoting chair, standing for the standing desk, verified by direct observation).…”
Section: Processingmentioning
confidence: 99%